ANALYSIS OF OUTPATIENT SATISFACTION FOR CIVIL SERVANT DURING THE IMPLEMENTATION OF ASKES AND JKN - Komang Trisnawati; Sumarni Sumarni; Achmad Fudholi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Patient satisfaction is one of indicator in determining whether a program run by the government considered success or not. The study aimed to determine the significant difference of gap between expectations and perceptions, and patient satisfactions on the quality of outpatient services during the Health Insurance (Askes) and the National Health Insurance (JKN) in Dr. Sardjito Hospital. This study used a cross-sectional method with purposive sampling on 100 civil servant outpatients. The research instrument was a questionnaire with Likert scale. Patient satisfaction was measured using SERVQUAL method for comparing the patient’s expectations and perceptions of outpatient services. The differences between expectations and perceptions of Askes and JKN era were analyzed using the Wilcoxon test, while the differences in patient satisfaction tested using the Mann Whitney with 95% confidence level. The results showed that there was a significant difference between expectations and perceptions in each dimension of SERVQUAL during Askes and JKN era with p-value 0.000. The highest gap both in Askes and JKN era was the same dimension, reliability, with gap score -0,87 and -1,49 respectively. In addition, the results also revealed that there was a significant difference between respondent satisfaction during Askes and JKN era with p-value 0.004. The highest gap score between Askes and JKN was the dimention of reliability with the gap score 0,62.Keywords: satisfaction, health insurance, SERVQUAL